Implikasi Teori Belajar Kognitivisme terhadap Pembelajaran Bahasa Arab the Implications of Cognitive Learning Theory on Arabic Language Learning - Isop Syafei (Attractive : Innovative Education Journal, 2025)
This study aims to examine the application of cognitive theory in Arabic language learning and analyze its implications for the design, implementation, and evaluation of instruction, including its strengths and weaknesses. The method used is a literature review, examining various relevant and credible written sources. This approach is employed to gain a deeper understanding of the application of cognitive theory in the context of Arabic language learning. The analysis technique includes the processes of searching, selecting, critically evaluating, and thoroughly analyzing literature. The reliability and validity of the research are ensured through systematic and structured steps. The findings of the study show: (1) Cognitive theory supports Arabic language learning through strengthening mental processes, meaningful understanding, active participation, the use of metacognitive strategies, and the role of the teacher as a facilitator. (2) Cognitive-based learning aims to optimize students' cognitive processes through deep understanding, active participation, and the application of metacognitive strategies. Instructional design needs to be structured by considering information, context, and active language interaction. (3) The teacher and student roles are crucial in fostering collaborative interaction and using metacognitive strategies to support student understanding. (4) This theory influences the evaluation of learning through formative, authentic, understanding-based assessments and constructive feedback. (5) Its strengths encourage deep understanding and active participation, while its weaknesses overlook social and cultural aspects. Thus, this study integrates cognitive theory into Arabic language learning through meaningful understanding, active participation, metacognitive strategies, collaborative interaction, and context-based evaluation.